Pyruvate Potentially Superior to NAD+ and Senolytics in Healthy Aging - Fang-Qiang, Zhou (Emerging Trends in Disease and Health Research Vol. 2, 2022)
This review aimed at evoking attention of sodium pyruvate effects on healthy aging relative to the nicotinamide adenine dinucleotide oxidized form (NAD+) and senolytics. In last decades, healthy aging has become one of research hotspots in life science. It is well known that NAD+ level in cells decreases with aging and aging-related diseases. Several years ago, one of NAD+ precursors was first demonstrated with its new role in DNA damage repairing in mice, restoring old mice to their physical state at young ones. The finding encourages extensive studies in animal models and patients. NAD+ and its precursors have been popular products in nutrition markets. Alternatively, it was also evidenced that clearance of cellular senescence by senolytics preserved multiorgan (kidney and heart) function and extended healthy lifespan in mice. Subsequent studies confirmed findings in elderly patients subjected with idiopathic pulmonary fibrosis. The senolytic therapy is now focused on various diseases in animal and clinical studies. However, pyruvate, as both a NAD+ substitute and a new senolytic, may be advantageous, on the equimolar basis, over current products above in preventing and treating diseases and aging. Pyruvate-enriched fluids, particularly pyruvate oral rehydration salt, may be a novel intervention for diseases and aging besides critical care. Albeit the direct evidence that benefits healthy aging is still limited to date, pyruvate, as both NAD+ provider and senolytic agent, warrants intensive research to compare NAD+ or senolytics for healthy aging, specifically on the equimolar basis, in effective blood levels. This review briefly discussed the recognition of healthy aging by comparing NAD+ and Senolytics with sodium pyruvate from the clinical point of view.